The Effect of Using Story Completion Technique on Students' Speaking English Ability in Grade 9 at SMP Pembangunan Laboratorium UNP - Zola Aghna Vabiola; Dinovia Fannil Kher (Universitas Negeri Padang, 2023)
Speaking is one of the most essential abilities in learning English. Story completion is the right method in learning English speaking that the students being able to speak in class within a group. This Research is conducted to find the effect of the use of the story completion technique on students’ speaking English Ability in grade 9 at SMP Pembangunan Laboratorium UNP. The students of SMP Pembangunan Laboratorium UNP in grade 9 contributed to the study’s population. The population consisted of 80 students and class IX C was selected to be the sample in this study through the cluster random sampling method. Ten sessions of the treatment were given to the students including the pretest and posttest that were held to conduct this research. Researchers used an English-speaking test by retelling a narrative story to collect the data. Story completion helps the students increasing their interest to speak English. The result of the data analysis denote that the null hypothesis found in this study is rejected which means that the effect of using story completion technique in students’ speaking English ability does give a significant effect to increase the speaking English ability of the students,and is accepted as the study’s result.